CD8+ T Cells Contribute to the Development of Coronary Arteritis in the Lactobacillus casei Cell Wall Extract–Induced Murine Model of Kawasaki Disease. Issue 2 (February 2017) - Noval Rivas, Magali; Lee, Youngho; Wakita, Daiko; Chiba, Norika; Dagvadorj, Jargalsaikhan; Shimada, Kenichi; Chen, Shuang; Fishbein, Michael C.; Lehman, Thomas J. A.; Crother, Timothy R.; Arditi, Moshe
Abstract : Objective: Kawasaki disease (KD) is the leading cause of acquired heart disease among children in developed countries. Coronary lesions in KD in humans are characterized by an increased presence of infiltrating CD3+ T cells; however, the specific contributions of the different T cell subpopulations in coronary arteritis development remain unknown. Therefore, we sought to investigate the function of CD4+ and CD8+ T cells, Treg cells, and natural killer (NK) T cells in the pathogenesis of KD. Methods: We addressed the function of T cell subsets in KD development by using a well‐established murine model of Lactobacillus casei cell wall extract (LCWE)–induced KD vasculitis. We determined which T cell subsets were required for development of KD vasculitis by using several knockout murine strains and depleting monoclonal antibodies. Results: LCWE‐injected mice developed coronary lesions characterized by the presence of inflammatory cell infiltrates. Frequently, this chronic inflammation resulted in complete occlusion of the coronary arteries due to luminal myofibroblast proliferation (LMP) as well as the development of coronary arteritis and aortitis. We found that CD8+ T cells, but not CD4+ T cells, NK T cells, or Treg cells, were required for development of KD vasculitis. Conclusion: The LCWE‐induced murine model of KD vasculitis mimics many histologic features of the disease in humans, such as the presence of CD8+ T cells and LMP in coronary artery lesions as well as epicardial coronary arteritis. Moreover, CD8+ T cells functionally contribute to the development of KD vasculitis in this murine model. Therapeutic strategies targeting infiltrating CD8+ T cells might be useful in the management of KD in humans.